Some Difficulties of Teaching Arabic Language from the Perspective of Teachers at First Basic Stage in Hama City. (Journal of Hama University, 2022)
The study aimed at recognizing the difficulties that teachers of First Stage face in teaching Arabic Language according to their viewpoints. The variables of study are gender, teaching expertise, and training courses. The research used the analytic descriptive approach. The researcher designed a questionnaire of 30 items to apply on a sample of (150) male/female teachers in Hama city.The results showed that:-      Difficulties of classroom environment came first, especially pupils' numbers inside classroom.-      Difficulties concerning teachers came last. The most serious difficulty was lack of learning resources.-      Difficulties of learners were most in shyness and introvertion.-      Difficulties of syllabus were most in the intensity and size of booktexts.-      The results of the study hypotheses indicated that there were no statistically significant differences between teachers in terms of a variable (gender, number of years of experience, and followed training courses).
Keywords: Difficulties of teaching Arabic language, Teachers of First Stage.